Genetic evaluation of first lactation production and reproduction traits in Sahiwal cattle - P.Kathiravan; G.K. Sachdeva; R.S. Gandhi; T.V. Raja; P.K. Singh; A.K. Singh (Journal of Livestock Biodiversity, 2025)
The present study was conducted on first lactation production and reproduction performance of Sahiwal cattle from NDRI, Karnal and Government Livestock Farm, Chakganjaria, Lucknow. First lactation records of 894 Sahiwal cows born to 60 sires, spread over a period of 33 years from 1973 to 2005 were utilized for the present study. The overall least squares mean of first lactation traits viz. AFC, FLL, FLMY, FL305DMY, FSP, FDP and FCI were estimated to be 1234.97±16.3 days, 322.21±6.82 days, 1785.32±49.49 kg, 1526.11±34.97 kg, 239.74±11.98 days, 201.63±11.05 days and 523.84±11.99 days respectively. The estimates of first lactation production traits, except FLL, were significantly higher in Karnal herd while all the first lactation reproduction traits were significantly higher in Lucknow herd. Season effect was not significant on most of the first lactation traits except first dry period. In contrast, different periods of calving were found to have significant influence on all the traits except first calving interval and first service period. Similarly, interaction of herd and period was found to have significant effect on all the first lactation traits while herd x season and period x season interactions were not found to have any significant influence for most of the traits. The heritability estimates of different first lactation production traits were moderate while the estimates for different reproduction traits were low except for age at first calving. In conclusion, the mean performance of different first lactation production and reproduction traits was comparatively better in Karnal than that of Lucknow herd. However, there seems to be a decreasing trend in production performance of both the herds.